2003
DOI: 10.5194/acp-3-161-2003
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the development of the Master Chemical Mechanism, MCM v3 (Part A): tropospheric degradation of non-aromatic volatile organic compounds

Abstract: Abstract. Kinetic and mechanistic data relevant to the tropospheric degradation of volatile organic compounds (VOC), and the production of secondary pollutants, have previously been used to define a protocol which underpinned the construction of a near-explicit Master Chemical Mechanism. In this paper, an update to the previous protocol is presented, which has been used to define degradation schemes for 107 non-aromatic VOC as part of version 3 of the Master Chemical Mechanism (MCM v3). The treatment of 18 aro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
1,570
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 1,430 publications
(1,634 citation statements)
references
References 101 publications
(109 reference statements)
56
1,570
7
1
Order By: Relevance
“…The model includes recent updates to the chemistry scheme to include bromine chemistry (Parella et al, 2012;Schmidt et al, 2016) and iodine chemistry (Sherwen et al, 2016a, b). Sources of tropospheric bromine in the model include emissions of CHBr 3 , CH 2 Br 2 and CH 3 Br, and transport of reactive bromine from the stratosphere.…”
Section: Global Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The model includes recent updates to the chemistry scheme to include bromine chemistry (Parella et al, 2012;Schmidt et al, 2016) and iodine chemistry (Sherwen et al, 2016a, b). Sources of tropospheric bromine in the model include emissions of CHBr 3 , CH 2 Br 2 and CH 3 Br, and transport of reactive bromine from the stratosphere.…”
Section: Global Modelmentioning
confidence: 99%
“…Sources of tropospheric bromine in the model include emissions of CHBr 3 , CH 2 Br 2 and CH 3 Br, and transport of reactive bromine from the stratosphere. Debromination of sea-salt aerosol is not included in the model following the work of Schmidt et al (2016), which showed better agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free troposphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). Emission rates and bromine chemistry included in the model are described in detail by Parella et al (2012), with the bromine chemistry scheme described by 19 bimolecular reactions, 2 threebody reactions and 2 heterogeneous reactions using rate coefficients, heterogeneous reaction coefficients and photolysis cross sections recommended by Sander et al (2011).…”
Section: Global Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, current schemes have not been tested against or constrained by measurements of multigenerational products (or classes of products) under realistic ambient conditions. Multi-generational VOC oxidation, in theory, can be explicitly modeled using detailed gas-phase chemical mechanisms such as the MCM (Master Chemical Mechanism; Jenkin et al, 2003;Saunders et al, 2003) or GECKO-A (Generator of Explicit Chemistry and Kinetics of Organics in the Atmosphere; Aumont et al, 2005;Camredon et al, 2007) and have been put to use to develop a better understanding of the reaction chemistry leading to SOA formation (Yee et al, 2012;Aumont et al, 2012;Valorso et al, 2011). However, these mechanisms track thousands to millions of chemical species and are computationally impractical for modeling multi-generational oxidation in 3-D models.…”
Section: Introductionmentioning
confidence: 99%